Cerebral correlates of faking: evidence from a brief implicit association test on doping attitudes - Schindler, Sebastian; Wolff, Wanja; Kissler, Johanna M.; Brand, Ralf (Frontiers in Behavioral Neuroscience, 2015)
Direct assessment of attitudes toward socially sensitive topics can be affected by deception attempts. Reaction-time based indirect measures, such as the Implicit Association Test (IAT), are less susceptible to such biases. Neuroscientific evidence shows that deception can evoke characteristic ERP differences. However, the cerebral processes involved in faking an IAT are still unknown. We randomly assigned 20 university students (15 females, 24.65 ± 3.50 years of age) to a counterbalanced repeated-measurements design, requesting them to complete a Brief-IAT (BIAT) on attitudes toward doping without deception instruction, and with the instruction to fake positive and negative doping attitudes. Cerebral activity during BIAT completion was assessed using high-density EEG. Event-related potentials during faking revealed enhanced frontal and reduced occipital negativity, starting around 150ms after stimulus presentation. Further, a decrease in the P300 and LPP components was observed. Source analyses showed enhanced activity in the right inferior frontal gyrus between 150 and 200ms during faking, thought to reflect the suppression of automatic responses. Further, more activity was found for faking in the bilateral middle occipital gyri and the bilateral temporoparietal junction. Results indicate that faking reaction-time based tests alter brain processes from early stages of processing and reveal the cortical sources of the effects. Analyzing the EEG helps to uncover response patterns in indirect attitude tests and broadens our understanding of the neural processes involved in such faking. This knowledge might be useful for uncovering faking in socially sensitive contexts, where attitudes are likely to be concealed.